“Efecto de la aplicación de fosfonato de calcio y boro en el cultivo de col china (brassica campestris L.) variedad kiboho 90 F-1, en el distrito de Lamas” - Dávila Lavi, Harvey Charles (2015)
The present research aimed to evaluate and determine the dose more phosphonate effect of Calcium and Boron on yield and crop yield of Chinese cabbage (Brassica campestris) Pequinensis range 90 F-1 in the district of Lamas and and perform economic analysis of each treatment. The grounds of "The Pacific" farm owned by Mr. Jorge Luis Pelaez Rivera was the place of execution of this research, politically located in the district and province of Lamas, department of San Martin. Statistical Design randomized complete block (RCBD) with three blocks and five treatments was designing this research has used with 15 experimental units. Using SPSS 19 statistical software processed the information gathered in the field, which uses the P - value comparison significant at confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANOVA) and multiple range test of Duncan P s 0.05. The variables evaluated were : plant height (cm ), stem diameter (cm ) diameter pela (cm), weight of the strips ( g ), yield ( kg ha- 1) and economic analysison. October 1, 2013 was the date of execution of planting in the nursery, staying 15 days. October 16, 2013 was the date of execution of the final field planting. The results indicate that evaluated a witness and four doses of Calcium and Boron phosphonate, in order to obtain the highest yield and economic benefit. lt determined as the most effective T 4 treatment with doses of 1.0 l.ha phosphonate -1 Calcium and Boron, who reported the highest performance and production as wefl as the economic benefit with 203, 711.20 kg ha- 1 and with a value B I C of 0.133 anda net profit of S /.27125.85 soles, respectively. Keywords: Assess, identify, dosage, yield, production, phosphonate calcium and boron, culture, Chinese cabbage.